Evaluating drivers of female dominance in the spotted hyena - McCormick, S. Kevin; Laubach, Zachary M.; Strauss, Eli D.; Montgomery, Tracy M.; Holekamp, Kay E. (Frontiers in Ecology and Evolution, 2022)
Dominance relationships in which females dominate males are rare among mammals. Mechanistic hypotheses explaining the occurrence of female dominance suggest that females dominate males because 1) they are intrinsically more aggressive or less submissive than males, and/or 2) they have access to more social support than males. Here, we examine the determinants of female dominance across ontogenetic development in spotted hyenas (Crocuta crocuta) using 30 years of behavioral observations from the Mara Hyena Project to evaluate these two hypotheses. Among adult hyenas, we find that females spontaneously aggress at higher rates than males, whereas males spontaneously submit at higher rates than females. Once an aggressive interaction has been initiated, adult females are more likely than immigrant males to elicit submission from members of the opposite sex, and both adult natal and immigrant males are more likely to offer a submission in response to an aggressive act than adult females. We also find that adult male aggressors are more likely to receive social support than are adult female aggressors, and that both adult natal and immigrant males are 2-3 times more likely to receive support when attacking a female than when attacking another male. Across all age classes, females are more likely than males to be targets of aggressive acts that occur with support. Further, receiving social support does slightly help immigrant males elicit submission from adult females compared to immigrant males acting alone, and it also helps females elicit submission from other females. However, adult females can dominate immigrant males with or without support far more often than immigrant males, even when the immigrants are supported against females. Overall, we find evidence for both mechanisms hypothesized to mediate female dominance in this species: 1) male and female hyenas clearly differ in their aggressive and submissive tendencies, and 2) realized social support plays an important role in shaping dominance relationships within a clan. Nevertheless, our results suggest that social support alone cannot explain sex-biased dominance in spotted hyenas. Although realized social support can certainly influence fight outcomes among females, adult females can easily dominate immigrant males without any support at all.